Is Annona lutescens a synonym of A. reticulata (Annonaceae)? Use of geometric morphometric and coloration data to solve this controversy - Ocampo, Gilberto; Castro-Moreno, Marisol (Instituto de Ecología, A.C., 2016)
Background and Aims: Annona lutescens was described in 1914 as a new species from Guatemala. Further studies allowed to locate this taxon in Chiapas, Mexico. However, some authors consider it as a synonym of A. reticulata, a species of American origin that is widely cultivated in many parts of the world. Leaf shape and fruit color are the original characters proposed to segregate these two species. The aim of this study was to evaluate whether both characters can be used to distinguish these taxa.Methods: Leaf shape was evaluated using a geometric morphometric approach. In addition, differences in fruit color and hypocotyl coloration of seedlings maintained in controlled environmental conditions were observed.Key results: The geometric morphometric analysis showed that the leaf shape of both species is very variable and that there is no significant difference between them. Fruit and hypocotyl coloration is specific to each species.Conclusions: It is suggested that A. lutescens should be treated as a synonym of A. reticulata until more evidence is obtained to clarify the relationships between them.